An uneven playing field: Rankings and ratings for economics in ERA 2010 - Bloch, Harry (Centre for Research in Applied Economics, 2012)
In the evaluation of research quality conducted under ERA 2010 the sub-disciplines of econometrics and theory were rated more highly than the sub-disciplines of applied economics and other economics. The rating in each sub-discipline was benchmarked against a world standard, so the results suggest that Australian economists produce relatively better econometric or theory research than applied or other economics research. However, closer examination of the processes on which the ratings were based suggests built-in biases that favour theory and econometric research over applied and other economics research, leaving the relative quality of research in the various sub-disciplines open to question.